On Some Difference Sequence Spaces Defined by Orlicz Function and Ideal Convergence in 2-Normed Space - Ghimire, Jhavi Lal; Pahari, Narayan Prasad (Nepal Journal of Mathematical Sciences, 2023)
See full text.